Articulating a transition pedagogy to scaffold and to enhance the first year student learning experience in Australian higher education. - Kift, Sally (Australian Learning and Teaching Council, 2009)
This ALTC Senior Fellowship sought to investigate and identify the research- and evidence-base necessary to promote a sectoral focus on good undergraduate first year curriculum design as a second generation FYE strategy (Gale, 2009; Wilson, 2009) in aid of commencing student learning, support, success, and retention. The Fellowship was framed around the articulation of a 'transition pedagogy' (Kift & Nelson, 2005) a guiding philosophy for intentional first year curriculum design and support that carefully scaffolds and mediates the first year learning experience for contemporary heterogeneous cohorts.